RUSSIANS IN ЕGYPT: ASPECTS OF RELIGIOUS AND CULTURAL IDENTIFICATION - M. A. Khalil (Концепт: философия, религия, культура, 2019)
The article studies mechanisms of preserving cultural and religious identity by the Russian residents in contemporary Egypt. Since the beginning of the XX century, three waves of Russian immigration to Egypt took place, each bearing its characteristic and unique features. Formation of the first sizeable Russian community in Egypt dates back to the beginning of the XX century when a number of the "White" emigrants from the Russian Empire, escaping from the October Socialist Revolution of 1917, arrived in Alexandria. The second wave of Russians, or Soviets to be precise, appears in Egypt starting from the beginning of 1960-es: after getting their higher education or academic degrees in the USSR young Egyptian men return to Egypt with their Russian wives. The third wave of Russian nationals emerge in Egypt from middle 1990-es due to a tremendously intensified tourist flow from Russia to Egypt: Russian females start travelling to the Red Sea resorts, particularly to Hurghada and Sharm-El-Sheikh, get acquainted with the Egyptian men working, as a rule, in tourism industry, get married and relocate to Egypt.The present day Russian community in Egypt is comprised predominantly from the so-called "Soviet" and "Russian" wives of the Egyptians, whose adaptation in a foreign cultural environment is analyzed according to the model suggested by Professor John Berry. He suggests that acculturation is being realized in four strategies: assimilation, separation, integration and marginalization. The study of acculturation strategies used by the Russian residents in contemporary Egypt reveals difference between the generation of "Soviets" and "Russians": the first category used mainly separation and rarely integration, while the second category on the contrary is characterized by a high degree of integration into the local social environment, while separation strategy could be rarely observed.